Ewangeliczne przypowieści wplecione w miesiące roku, czyli o cyklu akwafort Parabolae Christi Iesu in duodecim menses diggestae wydanym przez braci Klauberów (Tabularium Historiae, 2018)
An interesting series of etchings, depicting Gospel parables in the form of illustrations of the twelve months of the year, is housed at the National Library in Warsaw. Gottfried Bernhard Göz is the author of the model drawings. The series was issued circa 1770 by the well-known Klauber brothers fine art publishing house in Augsburg. Göz availed himself of some of the details contained in the descriptions of the parables in order to combine them with the months of the year, associating them with the farm work calendar cycle. As a matter of fact, Hans Bol did likewise almost two centuries earlier, creating drawings for copperplate engravings by Adriaen Collaert, issued by Jan Sadeler as part of the Emblemata evangelica ad XII signa coelestia sive totidem anni menses accomodata series. However, unlike the Flemish series, not just one but several Gospel events are combined with each month in the Augsburg etchings. Their selection does not correspond to the order of pericopes in the old liturgical calendar. Scenes illustrating diverse parables have been successfully combined on each of the prints. The artist also achieved a similar cohesiveness when combining illustrations of parables with country and urban landscapes, as well as with garden motifs.